Node self‐connections in network metrics. (1st December 2017) - Saura, Santiago
Abstract: Zamborain‐Mason et al . ( Ecol. Lett ., 20, 2017, 815–831) state that they have newly proposed network metrics that account for node self‐connections. Network metrics incorporating node self‐connections, also referred to as intranode (intrapatch) connectivity, were however already proposed before and have been widely used in a variety of conservation planning applications.